THE ANALYSIS PREDICTOR OF LANGUAGE DEVELOPMENT ACHIEVEMENT IN UNDER FIVE YEAR OLD CHILDREN - Tri Ratna Ningsih; Moh Alimansur; Ifa Roifah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
The difficulty of working mothers in stimulating the development of children's language was the lack of quality time for stimulation, the child was given a "leftover" time by the mother after the mother worked and the condition was tired after work. The study aimed to look for the predictor of language development achievement in under five years old children. The study design was analytic correlation. The study population was under five years old children with their mother (employed and unemployed) in Mojokerto District as many as 760 respondents. Sample of 102 respondents were taken using cluster random sampling. Sources of data used primary data, the instrument used a questionnaire and DDST, and collection of DDST data through observation. This research used logistic regression test. The Research result showed that mother’s job influenced children language development with the analysis result p-value 0,000 < 0,05, while the children’s gender also influenced their language development with p-value 0,046 < 0,05. From this research, it could be known that the working mothers had less time to motivate their children to learn a good language. Female children had a better language development than the male ones because female children had less activities